Measuring the Effect of Employment uncertainty on Fertility in Europe (A literature review) - Brian Buh (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2021)
Numerous studies have looked at the effect that employment uncertainty has on fertility/childbearing. However, there is a lack of consensus about how to conceptualise and measure it. This paper first reviews issues surrounding the conceptualisation and existing measures of employment uncertainty. It then reviews existing measure of employment uncertainty in the context of fertility decisions. Finally, it raises considerations about their use while suggesting directions for further study.
Keywords: 300; Employment uncertainty; fertility; job instability; measuring uncertainty